(3GdOQ GdeUhf aj Yde GdcJGH Gdecfhfs - (3TgGH GdOjf CHh GdYHGS CMeO Hf jhSa Hf YHO GdOGje GdSejf GdMdHj, GdSejf GdMdHj,J (B756 (3g` s
(3ChdgG (B:s
(3aXgQ aSGO gPG GdJNQjL s
(3BNQgG (B:s
(3eQGYGI dMGLHjg GdPi gh GdHOd bhdg s
(3GdLRA GdChd efgG ai ecJHI GdCSO HQbe (B12343s
(3GdLRA GdKGfj ef GdcJGHs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B260s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B122s
Keywords: (3GdJaSjQ hYdhe GdbQBfs